2016
DOI: 10.1038/nmeth.3958
|View full text |Cite
|
Sign up to set email alerts
|

Spliced synthetic genes as internal controls in RNA sequencing experiments

Abstract: RNA sequencing (RNA-seq) can be used to assemble spliced isoforms, quantify expressed genes and provide a global profile of the transcriptome. However, the size and diversity of the transcriptome, the wide dynamic range in gene expression and inherent technical biases confound RNA-seq analysis. We have developed a set of spike-in RNA standards, termed 'sequins' (sequencing spike-ins), that represent full-length spliced mRNA isoforms. Sequins have an entirely artificial sequence with no homology to natural refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
151
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(158 citation statements)
references
References 53 publications
0
151
0
Order By: Relevance
“…The inclusion of controls such as the External RNA Controls Consortium spike-in mixes (1 and 2) in different samples is another enhancement that would provide transcripts with known FCs as a further tool for assessing bias. The addition of spliced spike-in controls (52) is another alternative that would better tailor the experiment for benchmarking differential splicing methods.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of controls such as the External RNA Controls Consortium spike-in mixes (1 and 2) in different samples is another enhancement that would provide transcripts with known FCs as a further tool for assessing bias. The addition of spliced spike-in controls (52) is another alternative that would better tailor the experiment for benchmarking differential splicing methods.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing efforts in this context are illustrated by a recent call from the National Institute of Standard and Technology (https://federalregister.gov/a/2015-19742), to design an improved set of controls, which should (i) mimic endogenous RNA and (ii) not interfere with the measurement of endogenous RNA. More recently, [39] introduced sequins (sequencing spike-ins) — a set of extrinsic spike-ins designed for (bulk) RNA-seq experiments.…”
Section: Spike-in Sequences and Normalizationmentioning
confidence: 99%
“…This is due to the limited availability of high-quality, post-mortem human tissue and to technical limitations associated with standard approaches: most rely on short-read RNA-Seq and the reconstruction of fragmented sequences making the disambiguation of fulllength transcripts difficult, particularly for large and complex genes. Benchmarking studies have shown that short-read RNA-Seq methodologies are unable to accurately reconstruct and quantitate the majority of transcript and protein isoforms 22,23 .…”
Section: Introductionmentioning
confidence: 99%